2017
DOI: 10.1080/19420862.2017.1389355
|View full text |Cite
|
Sign up to set email alerts
|

Changes in complementarity-determining regions significantly alter IgG binding to the neonatal Fc receptor (FcRn) and pharmacokinetics

Abstract: A large body of data exists demonstrating that neonatal Fc receptor (FcRn) binding of an IgG via its Fc CH2-CH3 interface trends with the pharmacokinetics (PK) of IgG. We have observed that PK of IgG molecules vary widely, even when they share identical Fc domains. This led us to hypothesize that domains distal from the Fc could contribute to FcRn binding and affect PK. In this study, we explored the role of these IgG domains in altering the affinity between IgG and FcRn. Using a surface plasmon resonance-base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
61
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(72 citation statements)
references
References 53 publications
(40 reference statements)
8
61
0
Order By: Relevance
“…Human FcRn binding and protection is one of the dominant factors governing mAb PK in vivo, but the literature around the use of in vitro hFcRn binding assays for selecting or deselecting mAbs has provided conflicting results that often depend on assay format. [33][34][35][36][37] Piche-Nicholas et al 27 have recently observed a correlation of positive charge in the mAb variable region with affinity to immobilized human hFcRn using the same SPR format for which we have observed a strong correlation with hFcRn Tg32-projected human CL. A combined interaction with both hFcRn and the supporting matrix is likely responsible for the behavior we and others 13,27 have observed in immobilized hFcRn affinity chromatography, as well as in SPR.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…Human FcRn binding and protection is one of the dominant factors governing mAb PK in vivo, but the literature around the use of in vitro hFcRn binding assays for selecting or deselecting mAbs has provided conflicting results that often depend on assay format. [33][34][35][36][37] Piche-Nicholas et al 27 have recently observed a correlation of positive charge in the mAb variable region with affinity to immobilized human hFcRn using the same SPR format for which we have observed a strong correlation with hFcRn Tg32-projected human CL. A combined interaction with both hFcRn and the supporting matrix is likely responsible for the behavior we and others 13,27 have observed in immobilized hFcRn affinity chromatography, as well as in SPR.…”
Section: Discussionsupporting
confidence: 73%
“…A Biacore TM T100 or T200 (GE Healthcare) was used to measure the steady-state binding affinities of the interaction between IgG molecules and matrix-immobilized FcRn as previously described. 27,39 Briefly, 20-70 resonance units (RU) of biotinylated human FcRn-b2m complex were affinity captured on a carboxymethylated dextran chip pre-immobilized with streptavidin (SA) (GE Healthcare, #BR100531). A series of dilutions of IgG analytes (»100 mg total mAb) were prepared in sample buffer (20 mM MES, 150 nM NaCl, 3 mM EDTA, 0.5% Polysorbate 20, pH 6.0) and sequentially flowed over the FcRn coated SA chip.…”
Section: Fcrn Binding Affinity Methods Using Sprmentioning
confidence: 99%
See 1 more Smart Citation
“…Pregnancy-specific changes in glycosylation have been observed across both the Fc and the Fab domain of antibodies (Bondt et al, 2014;Jansen et al, 2016a;Sonneveld et al, 2016). However, glycosylated Fabs do not have the capacity to interact with FcRn, which binds to antibodies in the CH3 domain (Jensen et al, 2017;Piche-Nicholas et al, 2018), suggesting that only changes in Fc-glycosylation are likely to regulate placental selection. The potentially critical role of galactosylation for FcRn binding has been previously noted, likewise demonstrating enhanced FcRn binding to digalactosylated antibodies (Dashivets et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Notably, elimination appears to play a dominant role in PK and is under the influence of various regulation such as neonatal Fc receptor (FcRn)-dependent recycling, target-mediated drug disposition (TMDD), and non-specific or off-target bindingmediated clearance, among which FcRn-dependent recycling plays a major role (50,51). It has been demonstrated that TMDD leads to rapid clearance by inducing internalization and downstream degradation (50).…”
Section: Pharmacokinetics and Dosage Regimenmentioning
confidence: 99%